An approach on detection, quantification, technological properties, and trends market of A2 cow milk. (May 2023) - Dantas, Adriana; Kumar, Harsh; Prudencio, Elane Schwinden; de Avila, Lindiomar Borges; Orellana-Palma, Patricio; Dosoky, Noura S.; Nepovimova, Eugenie; Kuča, Kamil; Cruz-Martins, Natália; Verma, Rachna; Manickam, Sivakumar; Valko, Marian; et al.
Graphical abstract: Highlights: A2 β-casein from milk has some advantageous effects on the gastrointestinal tract. It is not fully agreed that A1 β-casein has a negative impact on health. The influence of β-casein variants on milk matrices should be better understood. UPLC-high-resolution MS and RT-PCR detecting adulteration of A2 milk products. "Organic A2 milk" represents a strong market trend for the coming years. Abstract: The genetic variant A2 β-casein integrates the casein protein group in milk and has been often associated with positive health outcomes. Therefore, this review explores the present understanding of A2 β-casein, including detection methods and the market trends for dairy from A2 milk. Also, the interaction of A2 β-casein with αs1 -casein and κ-casein genotypes was examined in terms of technological impacts on A2 milk. A limited number of preliminary studies has aimed to investigate the sensorial and technological impacts of β-casein variants in milk matrices, for instance, in yogurt and other derivatives. Nevertheless, considering studies carried out so far, it is concluded that the manufacture of dairy products from A2 milk is perfectly feasible, as the products presented slight differences when compared to those derived from traditional milk. In one of the works, sensitive drops in rennet coagulation time and curd firmness values were observed in cheese traits. However, it is relevant to point out that variant A of κ-casein plays a negative role in the coagulation features of milk. Therefore, alterations in the pattern of cheese-making properties are not uniquely related to β-casein variants. Attempts to produce A2 β-casein in laboratory (non-natural source), through biosynthesis, for example, have not been found so far. This knowledge gap offers a promising area for future studies concerning proteins and bioactive peptide production.